Dealing with unlawful sources of fund among Islamic banks in Malaysia: finding from the practitioners’ perspective - Hj Ibrahim, Badruddin; Che Mohd Salleh, Marhanum; Mohd, Azizah; Laeba, Muhammad (2018)
This study examines the issue of dealing with unlawful sources of fund among Islamic Banks in Malaysia from the practitioners’ perspective. It investigates the practice of the bank in Malaysia in dealing with unlawful sources of fund with respect to accepting deposit for safe keeping and investment and providing financial facilities to customers whose incomes come from unlawful sources. This is regardless whether the source of fund is wholly unlawful or the mixing between lawful and unlawful. Quantitative methodology is adopted to collect data among the industry practitioners those having direct involvement with the Islamic banks mainly officers of Shari’ah department, Shari’ah committee, and also related stakeholders of Islamic banks. Based on simple descriptive analysis, it is found that majority of the respondents have similar view that when the sources of fund is deemed unlawful, the bank cannot accept any deposit, investment, or give financing to the customers. With respect to the mixture sources of fund or activities, lawful and unlawful, it should not be restricted to receive the fund either for safe keeping, investment, or payment of financing. It is also confirm that the bank have right to investigate the sources of fund of the customers whether it is derived from Shari’ah compliant, non-Shari’ah compliant, or a mixture between the two.